DINAMIKA COPING STRESS KELUARGA DALAM MENGHADAPI ANAK YANGMENGALAMI HIDROSEFALUS - Yunita Handayani; Erlyn Erawan (Universitas Katolik Widya Mandala Surabaya, 2018)
Hydrocephalus is a nerve-cell damage that caused by excess fluid in the brain. This disease could cause problem in the balance, motoric movement, cognitive and child’s emotion during growth. A child with hydrocephalus must acquire a medical treatment appropriately to avoid negative effects of physical and death. Because of that, a child demands a brain surgery. Treatment processes require expensive costs, with a result that could have an effect on the family’s economic condition. In addition, the family also gets rejection from the environment because of the child’s condition that is different from the other children. The condition induces distress symptoms on the family. To reduce distress, the family needs to have an ability to change their cognition and behaviour. The ability is known as coping-stress. This research is aimed to understand dynamics of family’s coping-stress when raising their child with hydrocephalus. This research was conducted using a qualitative method with a case study approach, performed using an in-depth interview technique. Criteria being used to select informant in this research are family members who took care of the child during early diagnosis until this time, family members had a child with hydrocephalus' diagnosis of the birth, and people who understood the child’s conditions. The result revealed that the dynamics of family’s coping-stress could be seen from family’s way to surrender to God about the illness and their tendency to avoid a negative response from environment (emotion-focused coping). All informants also looked for information about the disease, followed through the treatment and the recovery (problem-focused coping). In this research, social support also influences how to care for the child and how to apply coping stress. Keyword: Stress, coping-stress, hydrocephalus, family